The epidemiology of macroeconomic expectations - Christopher D. Carroll (The Johns Hopkins University, Department of Economics, 2001)
Since the foundational work of Keynes (1936) macroeconomists have emphasized the importance of agents' expectations in determining macroeconomic outcomes Yet in recent decades macroeconomists have devoted almost no effort to modeling actual empirical expectations data instead assuming all agents' expectations are rational This paper takes up the challenge of modeling empirical household expectations data and shows that a simple standard model from epidemiology does a remarkably good job of explaining the deviations of household inflation and unemployment expectations from the rational expectations benchmark Furthermore a microfoundations or agent-based version of the model may be able to explain in a way that still permits aggregation stark rejections of the pure rational expectations framework like Souleles's (2002) finding that members of different demographic groups have sharply different predictions for macroeconomic aggregates like the inflation rate
Keywords: E0; E3; 330; flation; expectations; unemployment; monetary policy; agent-based modeling; Erwartungstheorie; Inflationserwartung; Inflation; Arbeitslosigkeit; Schätzung; USA